“Shrimp Watching” Ecotourism in Thailand: Toward Sustainable Management Policy - Hongjamrassilp, Watcharapong; Traiyasut, Prapun; Blumstein, Daniel T. (Frontiers in Conservation Science, 2021)
Interest in wildlife ecotourism is increasing but many studies have identified detrimental effects making it unsustainable in the long run. We discuss a relatively new wildlife ecotourism event where tourists visit Ubon Ratchathani, Thailand to witness a mass migration of freshwater shrimp that emerge from the water and move across land known as “shrimp parading”. As this has been developed into a tourist event, the number of migrating shrimp have declined, suggesting that it may be unsustainable as currently practiced. We used a questionnaire to ask how locals, tourists, and stakeholders value the shrimp and their willingness to change their behavior to mitigate anthropogenic impacts. We found that three groups of participants were not aware of potential negative impacts to the shrimp from tourism. Locals valued the tourism in terms of the economy, culture, and environment less than tourists and stakeholders. The local government applied a top-down approach to manage this tourism without a fundamental understanding of the shrimp’s biology, impacts of tourists on the shrimp, or the various stakeholder perceptions. We discuss the problems and possible solutions that may be employed to help sustain this fascinating biological and cultural event and propose a framework to develop a sustainable wildlife ecotourism management plan. This case study serves as a model for others developing wildlife watching ecotourism, especially in developing countries.